2019
DOI: 10.1007/s40333-019-0093-7
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological and economic feasibility of mitigating a stressed coastal aquifer using managed aquifer recharge: a case study of Jamma aquifer, Oman

Abstract: This study explored the hydrological and economic feasibility of managed aquifer recharge (MAR) using tertiary treated wastewater (TWW) to mitigate salinity in the coastal aquifer of Jamma, Oman. A steady-state groundwater flow and transport model, using MODFLOW software, was developed and calibrated. Different managerial scenarios were simulated and the results reveal that the Jamma aquifer will be further deteriorated in the next 20 a if it remains unmanaged. The groundwater table will decline further by mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…MAR using TSE represented a promising and potential option in the management of water resources in the Kingdom of Bahrain. It increased the groundwater level and reduced the salinity [66,67]. However, Ahmed et al [66] have suggested that before implementing this method of MAR proper attention must be given to health, environmental, ecological, aesthetics, financial, economic, political, and social losses.…”
Section: Soil Aquifer Treatment (Sat)mentioning
confidence: 99%
“…MAR using TSE represented a promising and potential option in the management of water resources in the Kingdom of Bahrain. It increased the groundwater level and reduced the salinity [66,67]. However, Ahmed et al [66] have suggested that before implementing this method of MAR proper attention must be given to health, environmental, ecological, aesthetics, financial, economic, political, and social losses.…”
Section: Soil Aquifer Treatment (Sat)mentioning
confidence: 99%
“…e marine economy indicates the status of various industrial activities for developing, utilizing, and protecting the oceans and the associated economic activities [39]. By referring to relevant research results [12][13][14][15][16][17], this study carried out a comprehensive analysis from the perspectives of the degree of development and quality of the marine economy. e specific indicator system is presented in Table 3. (1) e degree of development of the marine economy was measured by three indicators: total marine GDP, port cargo throughput, and coastline economic density.…”
Section: Indicator System For Marine Economy Developmentmentioning
confidence: 99%
“…Research on marine economies has long been under development and mainly includes (1) research on marine economies [8][9][10] and the vulnerability and stability of the marine economic system [11][12][13][14] based on sustainable development; (2) research related to the efficiency [15,16] and transformation [17] of marine economies; and (3) research on the relationship between marine economies and the environment [18], resource development [12], and marine industries [19][20][21][22][23]. In 2011, the concept of intensive sea use was officially proposed [24], and it has been gradually applied to relevant practical research on the development and utilization of sea areas.…”
Section: Introductionmentioning
confidence: 99%
“…The SAT is becoming a common practice in arid and semi-arid regions to produce water with acceptable quality [4,5]. It has been carried out in many countries around the world [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%